"Anyone Who Inspects the World Around Him Is in Some Measure a Geographer": Pasolinian Contributions to an Ecology of the Edges. Issue 1 (2nd January 2022) - Matthey, Laurent
Abstract : In a 1947 paper, John K. Wright proposed the term "geosophy" to capture "the study of geographical knowledge from any or all points of view, " a discipline that would explore all "geographical ideas, " both "true and false." This geosophy has led to a certain interest in parallel, imaginary or popular geographies. In the field of French-language geography, it will continue late in the day in a questioning of para-geographies produced by amateur or nonacademic geographers, rather close to certain Anglo-Saxon debates relating to popular geographies. His article attempts to reverse this point of view by turning these para-geographies into legitimate theories of space that are not recognized as such, as they are stated in a language other than that of science. It is a more poetic language, which resorts to allusion, implicit and imagery, whereas scientific writing prefers clarity, explicitness and factuality. As a result, these parallel geographies have not been elevated to the rank of a certain scientific dignity by the institution of geography and, more broadly, the sciences interested in the territory. I explore here some of Pier Paolo Pasolini's productions by focusing on the geographical knowledge of which they are both the product and the vector. To do so, I mobilize literary and film materials from his oeuvre. If Pasolini was not a researcher, as defined by academia, he was at least someone who was searching. His work, which aimed at broadening reflection on the way society functions, with a view toward its spatial organization, might have contributed to geographic knowledge.